Environmental Analysis in Determining The Direction of The Organization at MTs Darul Musthofa Lebak District Banten Province - Abdullah, Wawan; Ilzamudin, Ilzamudin; Shobri, Shobri (Mudir : Jurnal Manajemen Pendidikan, 2024)
Environmental analysis and determining the direction of the organization are two interrelated things in strategic management. Environmental analysis helps an organization to understand the internal and external factors that affect its success, while determining the direction of the organization is a process that involves choosing the most suitable strategy to take advantage of opportunities and overcome challenges faced by the organization. Steps that can be taken in carrying out an environmental analysis and determining the direction of the organization: Identify internal and external factors; Evaluation of internal and external factors; SWOT analysis; Determine the vision and mission of the organization; Design a strategy; Strategy implementation; Evaluation and monitoring. In conclusion, environmental analysis and determining organizational direction are important processes in strategic management to achieve long-term goals and enhance organizational success. By paying attention to internal and external factors, organizations can develop appropriate strategies to take advantage of opportunities and overcome challenges they face. Based on research, the advantages and disadvantages of MTs Darul Mustafa comes from the internal environment. The contribution of students with academic and non-academic achievements, good facilities and infrastructure, accelerated degree programs, low madrasah management capacity, unequal organizational and principal conflicts. Opportunities and risks arising from external MTs Darul Mustafa covers Islamic boarding schools and religious community culture, public trust in their children's education, government policies that impose administrative demands on teachers, and the rapid development of information and communication technology. Darul Mustafa that can be implemented must continue to gain public trust, including planning the objectives of the madrasa that are appropriate to the needs of the community and the conditions of the times. Using a participatory approach with various parties including teachers, students, student caregivers and the community, through qualified teaching staff by providing training/support training, creating a conducive madrasah environment by minimizing conflicts in the internal environment, and completing madrasah facilities. and infrastructure as needed.